On the Sensitivity of the Level of Output to Savings: Embodiment and Disembodiment: A Clarificatory Note - Fisher, Franklin M.; Levhari, David; Sheshinski, Eytan (Quarterly Journal of Economics, 1969)
Journal Article On the Sensitivity of the Level of Output to Savings: Embodiment and Disembodiment: A Clarificatory Note Get access Franklin M. Fisher, Franklin M. Fisher Massachusetts Institute of Technology Search for other works by this author on: Oxford Academic Google Scholar David Levhari, David Levhari Hebrew University Search for other works by this author on: Oxford Academic Google Scholar Eytan Sheshinski Eytan Sheshinski Hebrew University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 83, Issue 2, May 1969, Pages 347–348, https://doi.org/10.2307/1883092 Published: 01 May 1969